2014
DOI: 10.1002/path.4407
|View full text |Cite
|
Sign up to set email alerts
|

Sequential expression of miR‐182 and miR‐503 cooperatively targets FBXW7, contributing to the malignant transformation of colon adenoma to adenocarcinoma

Abstract: Genetic changes in colon cancer are known to parallel the tissue abnormalities associated with the disease, namely adenoma and adenocarcinoma. The role of microRNA dysregulation in dysplastic progression, however, is not well understood. Here, we show that miR-182 and miR-503 undergo sequential up-regulation and drive the progression of colon adenoma to adenocarcinoma by cooperatively down-regulating the tumour suppressor FBXW7. We identified that increased expression of miR-182 is a feature of adenomas. A sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
42
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 30 publications
7
42
1
Order By: Relevance
“…2a), even though the biological function in cell proliferation is obviously significant. These results might indicate that the other miR-503 target gene, FBXW7 [27], is also involved in the regulation of proliferation in CRC cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2a), even though the biological function in cell proliferation is obviously significant. These results might indicate that the other miR-503 target gene, FBXW7 [27], is also involved in the regulation of proliferation in CRC cells.…”
Section: Discussionmentioning
confidence: 99%
“…High expression of miR-503 is significantly associated with shorter OS [19], since miR-503 inhibits the G2/M DNA damage checkpoint by suppressing reprimo, which is a downstream protein of tumor suppressor p53 [26]. Recently, Li et al [27] showed that miR-182 and miR-503 cooperatively targeted F-box/WD repeat-containing protein 7 (FBXW7), which normally functions as a cell cycle regulator in CRC cells. They also demonstrated that miR-503 contributed to the malignant transformation of colonic adenoma to adenocarcinoma, and high expression of miR-503 in CRC tended to shorten OS [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-223 is also inversely correlated with Fbw7 expression in human oesophageal cancer [78]. miR-182 and miR-503 together reduce Fbw7 expression in colon adenoma AAC1 cells and increase their tumourigenicity in nude mice [79]. miR-92 represses Fbw7 expression and stabilises c-Myc in B cells, although this must be balanced by an increase in its "sister" miR (encoded by the same polycistronic transcript), miR-19, to repress apoptosis if this is to cause malignant transformation [68].…”
Section: Fbw7 Gene Expressionmentioning
confidence: 94%
“…Previous studies have identified that miR-503 is abnormally expressed in retinal glioblastoma, adenoma, breast cancer, non-small cell lung cancer and hepatic cancer. Furthermore, it has been demonstrated that miR-503 targets phosphoinositide-3-kinase, p85 or inhibitor of nuclear factor κB kinase subunit β, regulates the Rho guanine nucleotide exchange factor 19, DDHD domain containing 2 and F-box and WD repeat domain containing 7 genes and initiates apoptosis, thus promoting the growth and differentiation of tumors and inhibiting the invasion and metastasis of tumors (18,(26)(27)(28)(29)(30)(31). This indicates that miR-503 serves important roles in different types of cancer.…”
Section: Discussionmentioning
confidence: 99%